2010
DOI: 10.1007/s10535-010-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and regeneration of Vigna radiata

Abstract: An efficient regeneration protocol via somatic embryogenesis was optimized for mung bean [Vigna radiata (L.) Wilczek; cv. Vamban 1]. Primary leaf explants were used for embryogenic callus induction in MMS medium (Murashige and Skoog salts with B5 vitamins) containing 2.0 mg dm -3 2,4-dichlorophenoxyacetic acid (2,4-D), 150 mg dm -3 glutamine and 3 % sucrose. Fast growing, highly embryogenic cell suspensions were established from 21-d-old calli in MMS medium supplemented with 0.5 mg dm -3 2,4-D and 50 mg dm -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It has also hampered the development and release of new cultivars by in vitro selection. Thus many efforts have been made to optimize protocols of in vitro regeneration in many legumes including alfalfa , common bean (Veltcheva et al, 2005), cowpea (Bakshi et al, 2012), chickpea (Tripathi et al, 2013), grass pea (Ochatt et al, 2002), lentil (Newell et al, 2006;Sarker et al, 2012), L. japonicus (Barbulova et al, 2005), M. truncatula (Duque et al, 2006), moth bean (Vigna aconitifolia) (Choudhary et al, 2009), mungbean (Sivakumar et al, 2010), pea (Zhihui et al, 2009), pigeonpea (Krishna et al, 2010) and soybean (Loganathan et al, 2010). Although in many cases, the recovery of fertile plants is still low, it allowed application of genetic transformation and other tissue culture derived techniques to generate genetic diversity such as somaclonal variation, in vitro mutagenesis, and wide hybridization in some legume species.…”
Section: In Vitro-based Breeding Approachesmentioning
confidence: 99%
“…It has also hampered the development and release of new cultivars by in vitro selection. Thus many efforts have been made to optimize protocols of in vitro regeneration in many legumes including alfalfa , common bean (Veltcheva et al, 2005), cowpea (Bakshi et al, 2012), chickpea (Tripathi et al, 2013), grass pea (Ochatt et al, 2002), lentil (Newell et al, 2006;Sarker et al, 2012), L. japonicus (Barbulova et al, 2005), M. truncatula (Duque et al, 2006), moth bean (Vigna aconitifolia) (Choudhary et al, 2009), mungbean (Sivakumar et al, 2010), pea (Zhihui et al, 2009), pigeonpea (Krishna et al, 2010) and soybean (Loganathan et al, 2010). Although in many cases, the recovery of fertile plants is still low, it allowed application of genetic transformation and other tissue culture derived techniques to generate genetic diversity such as somaclonal variation, in vitro mutagenesis, and wide hybridization in some legume species.…”
Section: In Vitro-based Breeding Approachesmentioning
confidence: 99%
“…Also, neither the role of the non-enzymatic ROS-producing mechanisms nor that of the different cell organelles in the oxidative stress promotion in leaves of auxin herbicide-treated plants has been studied. Given that auxin herbicide-induced XOD is localized in peroxisomes apart from chloroplasts (Corpas et al 2008), that ACOX is a peroxisomal enzyme (Gerhardt 1983, Palma et al 1991, that oxidative stress triggers peroxisome biogenesis (López-Huertas et al 2000), and that auxin herbicides induce peroxisome proliferation in animals (Espandiari et al 1995), we decided to study the oxidative metabolism in leaf peroxisomes of pea plants treated by the auxin herbicide 2,4-D, which is also a positive growth regulator in tissue cultures (Sivakumar et al 2010). To our knowledge, there are no studies on the effect of 2,4-D on the oxidative metabolism and the structure of leaf peroxisomes.…”
Section: Introductionmentioning
confidence: 99%
“…23 Regarding mannitol, sorbitol and PEG, their beneficial effects on somatic embryo maturation were previously reported in many plant species such as holm oak, mung bean and papaya. 24,25,26 Our findings indicated that incorporating PEG in culture medium at the concentration of 40 g l -1 gave the highest number of mature embryos. This is in good agreement with previous results on the Moroccan date palm cultivars Mejhoul and Najda, in which PEG improved somatic embryo maturation.…”
Section: Discussionmentioning
confidence: 60%